Bey Mustapha bouchlaghem Al-Masrati (1686-1734) And his efforts in Open of Oran I in 1708 - drai, Fatima (The Algerian Historical Journal, 2026)
The West's beylek had its specificity due to its strategic location and internal and external circumstances associated with internal disturbances, and external threats, these circumstances and factors imposed the existence of bayat able to control the situation and address threats and work to recover oran. Our article, entitled "Bey Mustapha bouchlaghem Al-Masrati (1686-1734 AD) and his efforts in Open of oran I 1708", revolves around the reign of Bey Mustapha Bouchlaghem al-Masrati and his efforts in expanding the borders of the Beylek, and in recapturing Oran from the Spanish occupation in 1708.